2009
DOI: 10.1097/01.pap.0000249925.76324.47
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Manifestations of Sedatives and Analgesics in the Critical Care Unit

Abstract: There are numerous sedatives and analgesics used in critical care medicine today; these medications are used on critically ill patients, many of whom have heart disease, including coronary artery disease or congestive heart failure. The purpose of this review is to recognize the effects of these medications on the heart. Studies that evaluated the effects of sedatives and analgesics on normal individuals or on those with heart disease were reviewed. Current choices for sustained sedation in the critically ill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 161 publications
0
19
0
1
Order By: Relevance
“…This corresponds to data deriving from clinical trials in adult medicine. In these trials, it was shown that propofol is effective in patients with left ventricular dysfunction caused by sepsis or myocardial infarction (32,33). The occurrence of ROS, however, is not the only fatal step towards cardiogenic shock and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to data deriving from clinical trials in adult medicine. In these trials, it was shown that propofol is effective in patients with left ventricular dysfunction caused by sepsis or myocardial infarction (32,33). The occurrence of ROS, however, is not the only fatal step towards cardiogenic shock and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify therapeutic options which specifically target the right steps in the pathophysiological cascade. Propofol seems to be a very promising agent in that context (11,33,36), but still has to prove its effectiveness in the human neonatal population. One major concern in this respect is propofol infusion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…GABA A receptor activation produces sedation and hypnosis, but limited analgesia and immobilisation (Grasshoff et al 2006). Etomidate is commonly used in human and veterinary medicine as a sedative and for inducing anaesthesia (Ching and Baum 2009;Darrouj et al 2009;Falk and Zed 2004;Sams et al 2008). One of the side effects of the drug in addition to respiratory and cardiovascular depression is suppression of adrenal steroidogenesis, thus leading to an inhibition of cortisol synthesis (Vanden Bossche et al 1984;Wagner et al 1984; man, cow and rat).…”
Section: Metomidatementioning
confidence: 97%
“…This hemodynamic deterioration sometimes leads to multiple organ failure in post operative period. [1] But there is no other diagnostic test to evaluate this emergency situation except a meticulous clinical observation of sustained hypotension with tissue hypoperfusion despite adequate left ventricular filling pressure and oliguria. The development of advanced technology in the line of treatment such as extracorporeal life support (ELS), a variation of cardiopulmonary bypass, can improve the outcomes of cardiogenic shock.…”
Section: Introductionmentioning
confidence: 99%